Drinking as routine practice among re-integrating National Guard and Reservists from Arkansas - Traci H. Abraham; Ann M. Cheney; Geoffrey M. Curran; Karen L. Drummond (Qualitative Research in Medicine & Healthcare)
Active duty enlisted military personnel are more likely to misuse alcohol than civilians – a pattern which persists even after the transition to civilian life. We used in-depth, substance use history interviews to elicit drinking trajectories from 54 re-integrating Army National Guard, Air Force Reserve and Army Reserve personnel from Arkansas with a history of problematic substance use. A hybrid inductive-deductive analytic approach revealed institutional norms, shared beliefs about drinking, and social values and expectations among military peers present in the context of military service that Veterans described as having shaped their drinking trajectories. Framing Veterans’ narratives vis-à-vis practice theory revealed the complex processes by which excessive drinking was embodied as routine practice during military service and subsequently reproduced in a very different post-deployment context, often with deleterious results. Elucidating these implicit processes suggested pro-active strategies for preventing problematic drinking by active duty personnel and improving the re-integration experiences of Veterans.